2005
DOI: 10.1161/01.cir.0000167553.49133.81
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Infarcted Myocardium by Intramyocardial Implantation of Ex Vivo Transforming Growth Factor-β–Preprogrammed Bone Marrow Stem Cells

Abstract: Background-Recent studies have shown that bone marrow-derived stem cells differentiate into the phenotype of cardiomyocytes in vivo and in vitro. We tried to regenerate infarcted myocardium by implanting ex vivo transforming growth factor (TGF)-␤-preprogrammed CD117 (c-kit)-positive (CD117 ϩ ) stem cells intramyocardially. Methods and Results-CD117ϩ cells were isolated from the bone marrow mononuclear cells of GFP-transgenic or normal C57/BL6 mice. The myogenic differentiation of CD117 ϩ cells was achieved by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
117
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 137 publications
(120 citation statements)
references
References 27 publications
3
117
0
Order By: Relevance
“…19,36 CD117-positive BMMSCs treated with TGF-b1 increased expression of cardiac markers, such as troponin I, troponin T, connexin-43, GATA-4, and NKx-2.5. 2 Our results show that TGF-b1 promotes ADSC cardiomyogenic differentiation in vitro. A recent study showed that coaxing treatment of autologous MSCs with appropriate growth factors prior to transplantation led in vitro expression of early cardiac markers and functional improvement in chronically infarcted myocardium.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…19,36 CD117-positive BMMSCs treated with TGF-b1 increased expression of cardiac markers, such as troponin I, troponin T, connexin-43, GATA-4, and NKx-2.5. 2 Our results show that TGF-b1 promotes ADSC cardiomyogenic differentiation in vitro. A recent study showed that coaxing treatment of autologous MSCs with appropriate growth factors prior to transplantation led in vitro expression of early cardiac markers and functional improvement in chronically infarcted myocardium.…”
Section: Discussionmentioning
confidence: 52%
“…2,39 A recent study showed that CD117-positive BMMSCs cultured with a low TGF-b1 concentration (5 ng ml À1 ) did not increase ALP activity in vitro and that osteoblast differentiation was induced by a higher TGF-b1 concentration (100 ng ml À1 ). 2 In the present study, ADSCs cultured with TGF-b1 (10 ng ml À1 ) for 2 weeks did not express osteonectin or osteopontin, bone-specific markers. ADSC osteogenic differentiation could be induced by a higher TGF-b1 concentration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, histologic analyses revealed newly regenerated myocardium in the left ventricular anterior wall after the implantation of TGF-beta-preprogrammed cells in comparison with untreated cells (Li et al, 2005). It is our opinion that the study of myogenic potential could be important to identify markers specific of stem cells in in vivo adult myocardium that may be used to purify these cells and evaluate their regenerative ability.…”
Section: Discussionmentioning
confidence: 99%